Selección Dinámica de Celda en los Enlaces Ascendente y Descendente de Redes Heterogéneas: Estudio de las Estratégias Acoplada y Desacoplada - Montesinos-Barrios, Soraya; Aguayo-Torres, María del Carmen; Martín-Vega, Francisco-Javier (My University, 2017)
Dynamic cell selection (DCS) and decoupled access are two disruptive candidate schemes for cell association in future 5G networks. DCS provides adaptation to fast channel variations, which results in potential performance enhancement. On the other hand, decoupled accesses cope with the difference between uplink and downlink transmissions aiming to maximize their performance. In this paper, we investigate the performance such access schemes for both the downlink and the uplink with fractional power control (FPC) and compare them with different combinations of their static and coupled counter parts. Results reveal that decoupled access yields to a great fairness degree in the uplink, while the cost to pay is a minor reduction on the average rate. Additionally, dynamic cell selection with decoupled access leads to a high improvement of both fairness and average rate in the downlink and uplink.
Keywords: Redes de ordenadores; Sistema de comunicaciones móviles; redes heterogéneas; selección dinámica de celda; asociación desacoplada; 5G